Analisis Dampak Tahap Perkembangan Membaca pada Anak dan Remaja - Muhamad Irgi Abdillah Az-zarkasyi; Mawar Dwi Aprillia Firdaus; Indah Fadilah Pelupessy; Mahmudah Fitriyah (Universitas 45 Surabaya, 2024)
This research aims to analyze the impact of reading development stages on children and adolescents in the context of literacy. By focusing on six stages of reading development, this research identifies the influence of each stage on reading ability, comprehension, and cognitive development in this age group. The research method involved observation, interviews, and reading skills testing on a sample of children and adolescents. Qualitative data analysis is used to describe understanding of reading development patterns and measure their impact on literacy. The results of this research can provide an in-depth view of how each stage of reading plays an important role in shaping literacy in early childhood and adolescence. It is hoped that these findings can provide guidance for educators, parents and researchers in understanding and supporting the process of learning to read at this critical stage. The results of this research found that the stages of reading development have a significant impact on the reading ability, comprehension and cognitive development of children and adolescents.